2000
DOI: 10.1542/peds.106.6.e76
|View full text |Cite
|
Sign up to set email alerts
|

Predicting HIV Disease Progression in Children Using Measures of Neuropsychological and Neurological Functioning

Abstract: ABSTRACT. Background. Neuropsychological testing and 2 measures of neurological status, cortical atrophy, and motor dysfunction were assessed for their usefulness in predicting human immunodeficiency virus (HIV) disease progression in infants, children, and adolescents who participated in Pediatric AIDS Clinical Trials Group Protocol 152 (PACTG 152).Methods. A cohort of 722 antiretroviral therapy-naive children with symptomatic HIV infection were assessed at study entry and at later intervals. Assessments incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 41 publications
(55 reference statements)
2
48
0
1
Order By: Relevance
“…On the other hand, malnutrition probably contributes to poorer psychomotor functioning. And finally, an earlier longitudinal study 4 showed that poor psychomotor functioning (the outcome of Abubakar et al's study) was a predictor of HIV ⁄ AIDS disease progression (a predictor in this study). The relationships between disease stage, nutritional status, and psychomotor development are likely to be intricately interrelated.…”
supporting
confidence: 55%
“…On the other hand, malnutrition probably contributes to poorer psychomotor functioning. And finally, an earlier longitudinal study 4 showed that poor psychomotor functioning (the outcome of Abubakar et al's study) was a predictor of HIV ⁄ AIDS disease progression (a predictor in this study). The relationships between disease stage, nutritional status, and psychomotor development are likely to be intricately interrelated.…”
supporting
confidence: 55%
“…Cognitive delay in HIVinfected children has been well documented in numerous studies with a variety of clinical manifestations. These include: behavioural impairments, learning impairments, lower intellectual function, poor ability in sequential processing, attentiondeficit disorders; and spatial memory impairment (Ruel, et al, 2012;Grover, et al, 2007;Willen, 2006;Chase, et al, 2000;Blanchette, et al, 2001;Pearson, et al, 2000;Boivin, et al, 1995;Gay, et al, 1995;Brouwers, et al, 1995;Mellins, et al, 1994;.…”
Section: Cognitive Delaymentioning
confidence: 99%
“…In the decade following the 1990s, studies started to be published in the United States and Puerto Rico using data from the Woman and Infants Transmission Study (WITS) (Nozyce, et al, 2006;Smith, et al, 2006;Llorente, et al, 2003;Macmillan, et al, 2003;Chase, et al, 2000;Smith, et al, 2000), the Pediatric AIDS Clinical Trials Group (Lindsey, et al, 2007;Pearson, et al, 2000), and from the Adolescent Master Protocol (Rice, et al, 2012). These studies were primarily concerned with describing the type of neurodevelopmental impairment.…”
Section: Antiretroviral Eramentioning
confidence: 99%
See 2 more Smart Citations